2023
DOI: 10.1200/jco.22.01273
|View full text |Cite
|
Sign up to set email alerts
|

Progression-Free Survival and Patterns of Response in Patients With Relapsed High-Risk Neuroblastoma Treated With Irinotecan/Temozolomide/Dinutuximab/Granulocyte-Macrophage Colony-Stimulating Factor

Abstract: PURPOSE Although chemoimmunotherapy is widely used for treatment of children with relapsed high-risk neuroblastoma (HRNB), little is known about timing, duration, and evolution of response after irinotecan/temozolomide/dinutuximab/granulocyte-macrophage colony-stimulating factor (I/T/DIN/GM-CSF) therapy. PATIENTS AND METHODS Patients eligible for this retrospective study were age < 30 years at diagnosis of HRNB and received ≥ 1 cycle of I/T/DIN/GM-CSF for relapsed or progressive disease. Patients with prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…According to the authors, longer time from first chemotherapy to therapy with m3F8 had no impact on EFS in a multivariate analysis ( p = 0.156), so the postponed implementation of immunotherapy caused by recovery time after ASCT should not negatively influence survival [ 28 ]. The authors do not report on subsequent therapies, but comparable OS for both groups in the study may also be strongly influenced by the more effective treatment of relapses, given a time-consistent trend for increased risk of relapse without MAT+ASCT (5-year EFS: 51% versus 65%, p = 0.128) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, longer time from first chemotherapy to therapy with m3F8 had no impact on EFS in a multivariate analysis ( p = 0.156), so the postponed implementation of immunotherapy caused by recovery time after ASCT should not negatively influence survival [ 28 ]. The authors do not report on subsequent therapies, but comparable OS for both groups in the study may also be strongly influenced by the more effective treatment of relapses, given a time-consistent trend for increased risk of relapse without MAT+ASCT (5-year EFS: 51% versus 65%, p = 0.128) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the non-randomized extension of the registration trial demonstrated lower grade 3-4 hematologic adverse events in sargramostim cycles vs IL-2 cycles. 27 Other studies demonstrated the benefit of adding dinutuximab plus sargramostim to chemotherapy for relapsed/ refractory HR-NB, 82,84,85 including patients previously treated with anti-GD2 therapy. 84,85 A more recent study explored earlier use of dinutuximab with GM-CSF as part of induction therapy in HR-NB and showed promising end-of-induction objective response rates of up to 87%.…”
Section: Clinical Datamentioning
confidence: 99%
“…27 Other studies demonstrated the benefit of adding dinutuximab plus sargramostim to chemotherapy for relapsed/ refractory HR-NB, 82,84,85 including patients previously treated with anti-GD2 therapy. 84,85 A more recent study explored earlier use of dinutuximab with GM-CSF as part of induction therapy in HR-NB and showed promising end-of-induction objective response rates of up to 87%. 87 Additional dinutuximab studies are summarized in Table S2.…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…1 Data from Children's Oncology Group modern era early-phase trials suggests that only one in five children with recurrent/refractory neuroblastoma will survive 4 years from time of trial enrollment. 2 Despite recent advances in combination chemotherapy and immunotherapy, 3 children with recurrent/refractory neuroblastoma often experience a high burden of distressing symptoms, and prior work has identified receipt of moderate or highintensity cancer-directed therapy as a contributor to suffering. 4 Parents often hold onto curative hopes and goals for their children with cancer in the face of progressing disease.…”
Section: Introductionmentioning
confidence: 99%